(untitled) (Dimensión Antropológica, 2019)
The aim of this article is to highlight a recurrent issue that affects fieldwork in Otomi villages: the difficulty, for an observer willing to assert his candid monological authority, to formulate research proposals acceptable to the academic community, while, at the same time, the native doxa considers all interactional space to be under the aegis of the Devil (Zithû). An anthropological theory is the result of a constructive elimination process that leads to the elaboration of a model that does not tolerate exceptions, which otherwise would lead to its complete collapse. In the present case, the Otomi Devil deconstructs any “good” theory by means of his nzahki, an exterior force found within humans, in the form of a labile and active component that feeds off their thinking and their actions. In Otomi terms, it is impossible to conceive of a stable cognitive function that is not contaminated by the actions of Zithû, who mocks any form of classification. He constantly gives contradictory opinions of truth, which, for the investigator, can be an almost insurmountable challenge when it comes to interpreting the data.